RELATIONSHIP BETWEEN PARENTING PATERNED PARENTS WITH RISKS ATTENTION DEFISIT HIPERAKTIVITY DISORDER (ADHD) PRESCHOOLES IN TK MENUR 1 SRUNI MUSUK BOYOLALI - Suyami Suyami (MOTORIK Jurnal Ilmu Kesehatan, 2018)
Background :Parenting is one of the environmental factors which affect the development of children, because parents are the closest to the child who will observe any progress, delays or disturbances that occur in the child. The most common developmental disorder occurs in preschool children in the field of psychiatry is Attention Defisit Hiperaktivity Disorder (ADHD). Objetive :The purpose of research is to know the relationship of parenting pattern with risk of Attention Defisit Hiperaktivity Disorder (ADHD) preschoolers in Tk Menur 1 Sruni Musuk Boyolali. Methods :This study were conducted in a cross-sectional analytic approach. The population in this study were all preschool children aged 4 to 6 years in Tk Menur 1 Sruni Musuk Boyolali. The number of sample are 59 people, the sample are taken using total sampling technique by using exclusion criteria. Instruments used were parenting questionnaires and early detection of ADHD risk questionnaires. The data analysis using chi square test. Result :Parenting pattern of parents in Tk Menur 1 Sruni Musuk Boyolali there are 33 respondents (55,9%) with authoritarian parenting, 8 respondents (13,6%) with permissive parenting pattern and 18 respondents (30,5%) With authoritative parenting. Children with GPPH risk were 39 respondents (66.1%) and 20 respondents (33.9%) normal. The result of chi square test shows that there is a relationship of parenting pattern with ADHD risk in preschool children in Tk Menur 1 Sruni Musuk Boyolali with p-value 0,001. Conclusion :The Conclusion is there a parenting relationship with risk of attention disorder concentration hyperactivity in preschool children at Tk Menur 1 Sruni Musuk Boyolali.